Warning: foreach() argument must be of type array|object, bool given in /var/www/html/web/app/themes/studypress-core-theme/template-parts/header/mobile-offcanvas.php on line 20

In Exercises 35–42, use the laws in Definition \(1\) to show that the stated properties hold in every Boolean algebra.

39. Show that De Morgan's laws hold in a Boolean algebra.

That is, show that for all \(x\) and \(y\), \(\overline {(x \vee y)} {\bf{ = }}\bar x \wedge \bar y\) and \(\overline {(x \wedge y)} = \bar x \vee \bar y\).

Short Answer

Expert verified

The given \(\overline {\left( {x \vee y} \right)} = \bar x \wedge \bar y\) and \(\overline {\left( {x \wedge y} \right)} = \bar x \vee \bar y\) is proved.

Step by step solution

01

Definition

Identity laws

\(\begin{array}{c}x \vee 0 = x\\x \wedge 1 = x\end{array}\)

Complement laws

\(\begin{array}{c}x \vee \bar x = 1\\x \wedge \bar x = 0\end{array}\)

Associative laws

\(\begin{array}{c}x \vee \left( {y \vee z} \right) = \left( {x \vee y} \right) \vee z\\x \wedge \left( {y \wedge z} \right) = \left( {x \wedge y} \right) \wedge z\end{array}\)

Distributive laws

\(\begin{array}{c}x \vee \left( {y \wedge z} \right) = \left( {x \vee y} \right) \wedge \left( {x \vee z} \right)\\x \wedge \left( {y \vee z} \right) = \left( {x \wedge y} \right) \vee \left( {x \wedge z} \right)\end{array}\)

De Morgan's laws

\(\begin{array}{c}\overline {\left( {x \vee y} \right)} = \bar x \wedge \bar y\\\overline {\left( {x \wedge y} \right)} = \bar x \vee \bar y\end{array}\)

02

 Step 2: Using the associative, commutative, complement, distributive and identity laws

To proof: \(\overline {\left( {x \vee y} \right)} = \bar x \wedge \bar y\)

PROOF

\(y\)is the complement of \(x\)if and only if \(x \vee y = 1\)and\(x \wedge y = 0\).

Note: The complement is also unique, which was proven in one of the previous solutions.

Thus, you need to show that \(\bar x \wedge \bar y\) is the complement of \(x \vee y\).

\(\begin{aligned}\left( {x \vee y} \right) \vee \left( {\bar x \wedge \bar y} \right) &=& \left( {y \vee x} \right) \vee \left( {\bar x \wedge \bar y} \right)\\& =& y \vee \left( {x \vee \left( {\bar x \wedge \bar y} \right)} \right)\\&=& y \vee \left( {\left( {x \vee \bar x} \right) \wedge \left( {x \vee \bar y} \right)} \right)\\ &=& y \vee \left( {1 \wedge \left( {x \vee \bar y} \right)} \right)\end{aligned}\)

\(\begin{aligned}&=& y \vee \left( {\left( {x \vee \bar y} \right) \wedge 1} \right)\\ &=& y \vee \left( {x \vee \bar y} \right)\\&=& y \vee \left( {\bar y \vee x} \right)\\&=& \left( {y \vee \bar y} \right) \vee x\end{aligned}\)

\(\begin{aligned}&=& 1 \vee x\\&=& x \vee 1\\& = &1\end{aligned}\)

03

Using the associative, commutative, complement, distributive and identity laws

\(\begin{aligned}\left( {x \vee y} \right) \wedge \left( {\bar x \wedge \bar y} \right) &=& \left( {\left( {x \vee y} \right) \wedge \bar x} \right) \wedge \bar y\\& =& \left( {\left( {x \wedge \bar x} \right) \vee \left( {y \wedge \bar x} \right)} \right) \wedge \bar y\\ &=& \left( {0 \vee \left( {y \wedge \bar x} \right)} \right) \wedge \bar y\\& =& \left( {\left( {y \wedge \bar x} \right) \vee 0} \right) \wedge \bar y\end{aligned}\)

\(\begin{aligned} &=& \left( {y \wedge \bar x} \right) \wedge \bar y\\ &=& \left( {\bar x \wedge y} \right) \wedge \bar y\\ &=& \bar x \wedge \left( {y \wedge \bar y} \right)\\ &=& \bar x \wedge 0\\ &=& 0\end{aligned}\)

Thus \(\bar x \wedge \bar y\) is the (unique) complement of \(x \vee y\).

Therefore, it gets \(\overline {(x \vee y)} {\bf{ = }}\bar x \wedge \bar y\)

04

Step 4:Using the associative, commutative, complement, distributive and identity laws

To proof: \(\overline {\left( {x \wedge y} \right)} = \bar x \vee \bar y\)

PROOF

\(y\)is the complement of \(x\)if and only if \(x \vee y = 1\)and\(x \wedge y = 0\). Note: The complement is also unique, which was proven in one of the previous solutions.

Thus, you need to show that \(\bar x \vee \bar y\) is the complement of \(x \wedge y\).

\(\begin{aligned}\left( {x \wedge y} \right) \wedge \left( {\bar x \vee \bar y} \right) &=&\left( {y \wedge x} \right) \wedge \left( {\bar x \vee \bar y} \right)\\ &=& y \wedge \left( {x \wedge \left( {\bar x \vee \bar y} \right)} \right)\\ &=& y \wedge \left( {\left( {x \wedge \bar x} \right) \vee \left( {x \wedge \bar y} \right)} \right)\\ &=& y \wedge \left( {0 \vee \left( {x \wedge \bar y} \right)} \right)\end{aligned}\)

\(\begin{aligned} &=& y \wedge \left( {\left( {x \wedge \bar y} \right) \vee 0} \right)\\ &=& y \wedge \left( {x \wedge \bar y} \right)\\ &=& y \wedge \left( {\bar y \wedge x} \right)\\ &=&\left( {y \wedge \bar y} \right) \wedge x\end{aligned}\)

\(\begin{aligned} &=&0 \wedge x\\ &=& x \wedge 0\\ = 0\end{aligned}\)

05

Using the associative, commutative, complement, distributive and identity laws

Using the associative, commutative, complement, distributive and identity laws

\(\begin{aligned}\left( {x \wedge y} \right) \vee \left( {\bar x \vee \bar y} \right) &=& \left( {\left( {x \wedge y} \right) \vee \bar x} \right) \vee \bar y\\ &=& \left( {\left( {x \vee \bar x} \right) \wedge \left( {y \vee \bar x} \right)} \right) \vee \bar y\\ &=& \left( {1 \wedge \left( {y \vee \bar x} \right)} \right) \vee \bar y\\ &=& \left( {\left( {y \vee \bar x} \right) \wedge 1} \right) \vee \bar y\end{aligned}\)

\(\begin{aligned} &=& \left( {y \vee \bar x} \right) \vee \bar y\\&=& \left( {\bar x \vee y} \right) \vee \bar y\\ &=& \bar x \vee \left( {y \vee \bar y} \right)\\ &=& \bar x \vee 1\\ &=& 1\end{aligned}\)

Thus,\(\bar x \vee \bar y\) is the (unique) complement of \(x \wedge y\).

Therefore, it gets \(\overline {(x \wedge y)} {\bf{ = }}\bar x \vee \bar y\)

Unlock Step-by-Step Solutions & Ace Your Exams!

  • Full Textbook Solutions

    Get detailed explanations and key concepts

  • Unlimited Al creation

    Al flashcards, explanations, exams and more...

  • Ads-free access

    To over 500 millions flashcards

  • Money-back guarantee

    We refund you if you fail your exam.

Over 30 million students worldwide already upgrade their learning with Vaia!

One App. One Place for Learning.

All the tools & learning materials you need for study success - in one app.

Get started for free

Most popular questions from this chapter

Construct a circuit for a full subtractor using AND gates, OR gates, and inverters. A full subtractor has two bits and a borrow as input, and produces as output a difference bit and a borrow.

Find a Boolean product of Boolean sums of literals that has the value 0 if and only if \({\bf{x = y = 1}}\) and \({\bf{z = 0,x = z = 0}}\) and \({\bf{y = 1}}\), or \({\bf{x = y = z = 0}}\). (Hint: Take the

Boolean product of the Boolean sums found in parts (a), (b), and (c) in Exercise 7.)

How many different Boolean functions \({\bf{F(x,y,z)}}\) are there such that \({\bf{F(\bar x,y,z) = F(x,\bar y,z) = F(x,y,\bar z)}}\) for all values of the Boolean variables \({\bf{x,y}}\), and \({\bf{z}}\)\({\bf{?}}\)

Exercises 14-23 deal with the Boolean algebra \(\left\{ {{\bf{0,1}}} \right\}\) with addition,multiplication, and complement defined at the beginning of this section. In each case, use a table as in Example \(8\).

22. Verify the unit property.

Use a \({\bf{K}}\)-map to find a minimal expansion as a Boolean sum of Boolean products of each of these functions in the variables \({\bf{w, x, y}}\) and \({\bf{z}}\).

\(\begin{array}{l}{\bf{a) wxyz + wx\bar yz + wx\bar y\bar z + w\bar xy\bar z + w\bar x\bar yz}}\\{\bf{b) wxy\bar z + wx\bar yz + w\bar xyz + \bar wx\bar yz + \bar w\bar xy\bar z + \bar w\bar x\bar yz}}\\{\bf{c) wxyz + wxy\bar z + wx\bar yz + w\bar x\bar yz + w\bar x\bar y\bar z + \bar wx\bar yz + \bar w\bar xy\bar z + \bar w\bar x\bar yz}}\\{\bf{d) wxyz + wxy\bar z + wx\bar yz + w\bar xyz + w\bar xy\bar z + \bar wxyz + \bar w\bar xyz + \bar w\bar xy\bar z + \bar w\bar x\bar yz}}\end{array}\)

See all solutions

Recommended explanations on Math Textbooks

View all explanations

What do you think about this solution?

We value your feedback to improve our textbook solutions.

Study anywhere. Anytime. Across all devices.

Sign-up for free